Antibacterial Effect of Methanol Extract of Newbouldia laevis Leaves on Some Selected Resistant Pathogen on Synthesised Drugs - Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen; Tansaba, Akafa Andes; Nanmar, Chakfa; Danjuma, Tyem Lawal; Umaru, Isaac John (Kwaghe International Journal of Sciences and Technology, 2024)
Newbouldia laevis is a tropical plant belonging to the family of Bignoniaceae. It is among the most useful plants in Africa. Historically medicinal plants have been provided a good source of inspiration for novel therapeutic drugs which has made a large contribution to health and well-being of humans. It has been used over the years to as curative agents against many infections and have been exploited in the traditional medicine with their curative potentials. Material and methods: The leaves of Newbouldia laevis was bought from a local market in Wukari, Taraba State. The leaves of Newbouldia laevis was chop into pieces, air-dried for four days and then pulverized into fine powder. About 250 g of the powdered bark extracted with 2 L of ethanol using maceration method for 72 hrs. The crude extracts of Newbouldia laevis was used in antibacterial assay. The results observed demonstrate that the Newbouldia leaves methanol crude extract possesses concentration-dependent antibacterial activity against both Gram-positive resistant bacteria (Staphylococcus aureus) and Gram-negative (Escherichia coli, Klebsiella pneumonia) bacteria. The increasing inhibition zones with higher concentrations suggest a potential dose-response relationship.